Is there a role for therapy response assessment with 2-[fluorine-18] fluoro-2-deoxy-d-glucose–positron emission tomography/computed tomography in mantle cell lymphoma?. Issue 11 (November 2014) - Kedmi, Meirav; Avivi, Irit; Ribakovsky, Elena; Benyamini, Noam; Davidson, Tima; Goshen, Elinor; Tadmor, Tamar; Nagler, Arnon; Avigdor, Abraham
Abstract 2-[Fluorine-18] fluoro-2-deoxy-d-glucose–positron emission tomography/computed tomography (FDG-PET/CT) scanning is used for response assessment in mantle cell lymphoma (MCL). However, its ability to predict outcome is debatable. We retrospectively evaluated the prognostic impact of interim and post therapy FDG-PET/CT scan on outcome of 58 consecutive MCL patients. Scans performed at diagnosis, mid-therapy, post-chemotherapy and post-transplant were reviewed and outcome analyzed. Median age was 59; MCL International Prognostic Index (MIPI) was low in 45%, intermediate in 41% and high in 14%. Thirty-four patients (58%) received R-CHOP (rituximab, cyclophosphamide, hydroxydaunorubicin, oncovin, prednisone) or R-CHOP-like chemotherapy, 24 (42%) underwent upfront autologous stem-cell transplant (ASCT). Three-year overall (OS) and progression-free-survival (PFS) were 81% and 45%, respectively. No differences in OS or PFS between PET-positive and PET-negative groups both for interim and post-therapy scans were observed. We conclude that in patients treated with R-CHOP, using the International-Harmonization-Project criteria for FDG-PET/CT interpretation, there is no role for interim or post-therapy PET.